2001
DOI: 10.1109/32.988709
|View full text |Cite
|
Sign up to set email alerts
|

Generating software test data by evolution

Abstract: This paper discusses the use of genetic algorithms (GAs) for automatic software test data generation. This research extends previous work on dynamic test data generation where the problem of test data generation is reduced to one of minimizing a function Miller and Spooner, 1976, Korel, 1990]. In our work, the function is minimized by using one of two genetic algorithms in place of the local minimization techniques used in earlier research. We describe the implementation of our GA-based system, and examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
268
1
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(291 citation statements)
references
References 28 publications
4
268
1
13
Order By: Relevance
“…Michael and McGraw generated a tool named GADGET to generate test data. The tool makes use of a branch table that keeps a track of all the branch conditions for both of their true and false parts [5].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Michael and McGraw generated a tool named GADGET to generate test data. The tool makes use of a branch table that keeps a track of all the branch conditions for both of their true and false parts [5].…”
Section: Related Workmentioning
confidence: 99%
“…Reliability based testing criteria are used to show the correctness of the program in terms of achieving some coverage that may be either 'control flow coverage' or 'Data flow coverage'. Control flow coverage criteria include path testing [4], condition testing [5], branch testing [6,7], etc. Data flow coverage criteria include all-uses [8], all-du (definition use) paths [9,23,26,27] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Micheal et al [22], Levin and Yehudai [25], Joachim et al [27] indicated that GA outperforms other SBTDG methods e.g. local search or random testing.However eventhough they can generate test data with appropriate fault-prone ability [4,5], they fail to produce them quickly due to their slowly evolutionary speed.…”
Section: Introduction *mentioning
confidence: 99%
“…Even though there have been significant achievements, SE still faces difficulties in handling infinite loops, array, procedure calls and pointer references in each PUT [22].…”
Section: Introduction *mentioning
confidence: 99%
“…Therefore, it is natural for the software engineering community to try to develop methods to reduce the cost associated with testing while enhancing the testing process. Since manual testing is expensive, time consuming and error prone, there has been significant interest in automation [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%